Strategi Efektif Membimbing Diskusi Kelompok Kecil Untuk Meningkatkan Kolaborasi Siswa - Dinil Arifah; Kholidah Nur; Amaliah Amaliah (Lembaga Pengembangan Kinerja Dosen, 2025)
Education in the era of globalization demands the development of students' social skills, including collaboration, to prepare them for the challenges of the 21st century. One effective method to train these skills is small group discussions, which encourage students to share ideas, listen to other perspectives, and reach consensus. This study aims to identify effective strategies in guiding small group discussions to improve student collaboration, focusing on the implementation of the Merdeka Curriculum. The research method used is qualitative descriptive with a case study design in one of the high schools that implements the Merdeka Curriculum. Data were collected through observation, interviews, documentation, and student collaboration questionnaires. The results of the study indicate that effective strategies include the use of open-ended questions, providing constructive feedback, and dividing roles in groups. In addition, the dynamics of small group discussions can be improved with good conflict management by teachers. This study also found that small group discussions can improve students' collaboration skills, which are reflected in communication, individual responsibility, and group decision making. Implications for the implementation of the Merdeka Curriculum show the importance of teacher training to improve the ability to guide small group discussions effectively. This study provides practical and theoretical contributions to the development of collaboration-based learning in Indonesia.